ANALISIS WACANA KEBIJAKAN : MAKAN BERGIZI GRATIS DALAM DISKURSUS PUBLIK - Arik Prayoga; Dian Prima Safitri; Chaerey Ranba Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Free Nutritious Meals (MBG) policy is one of the Indonesian government’s priority programs aimed at improving the nutritional quality of the population and supporting human resource development. In its implementation, this policy has elicited various public responses, ranging from support to criticism regarding the program’s effectiveness, targeting accuracy, food safety, and budget management. This study aims to understand how the government constructs the MBG policy discourse and to assess the relationship between government discourse and public discourse in the formation of policy legitimacy. The study employs a qualitative approach using the Discourse Network Analysis (DNA) method. Data were collected through a documentary analysis of official government documents, statements by officials, mass media reports, opinion pieces, and publications from relevant institutions. The analysis was conducted by identifying the actors, arguments, and positions that emerged in the discourse and mapping the relationships among actors in supporting or criticizing the MBG policy. The results show that the government constructs the MBG discourse as an investment in human development, an effort to combat stunting, and a driver of the local economy. Meanwhile, public discourse has evolved in the form of both support and criticism, focusing on food safety, program effectiveness, budget transparency, and the accuracy of beneficiary targeting. The interaction between these two discourses indicates that the legitimacy of the MBG policy is shaped not only by the government’s narrative but also by the public responses emerging within the discursive space. The government has addressed various criticisms by strengthening oversight, evaluating the program, and improving implementation standards. This study concludes that the sustainability and legitimacy of the MBG policy are significantly influenced by the government’s ability to establish communication that is responsive to the dynamics of public discourse.